2019
DOI: 10.1093/alcalc/agz042
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in Relation to Drinking Goals in Alcohol-Dependent Individuals: A Follow-up Study 2.5 and 5 Years After Treatment Entry

Abstract: Aims To evaluate the long-term treatment outcome (up to 5 years) with respect to different drinking goals of patients. Methods Alcohol-dependent individuals (n = 349) were recruited from three alcohol treatment units. They were interviewed using the Addiction Severity Index (ASI). They were sub-grouped according to their goal at treatment entry: abstinence, low- risk drinking and no decided goal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
11
0
3
Order By: Relevance
“…Psychologists were assigned to patients based on case‐load, and their fractional time appointment with the treatment service. Alcohol abstinence is considered the clinically optimal goal for severely dependent patients [1,45,46]. Some patients were prescribed adjunctive medication (Table 2) after consultation with a physician at treatment entry (acamprosate, naltrexone, both or CBT only).…”
Section: Methodsmentioning
confidence: 99%
“…Psychologists were assigned to patients based on case‐load, and their fractional time appointment with the treatment service. Alcohol abstinence is considered the clinically optimal goal for severely dependent patients [1,45,46]. Some patients were prescribed adjunctive medication (Table 2) after consultation with a physician at treatment entry (acamprosate, naltrexone, both or CBT only).…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that one-and two-level reductions in WHO risk levels would be achieved, associated with improved functional outcomes, and maintained over time in both the COMBINE and UKATT samples. Based on prior research showing that low risk drinking is more likely among individuals with lower alcohol dependence severity [12,[26][27][28], we hypothesized that reductions in WHO risk levels would be more likely to be achieved, associated with improved functional outcomes, and maintained over time among those with lower initial alcohol dependence severity.…”
Section: Who Risk Levels As a Drinking Reduction Targetmentioning
confidence: 99%
“…The inclusion of harm reduction end-points is important, because most individuals who receive treatment for AUD have difficulty sustaining abstinence [4][5][6] and many individuals with AUD prefer drinking reduction goals [7][8][9][10][11]. However, questions remain regarding whether non-abstinent drinking reductions can be achieved and maintained, particularly among individuals with more severe AUD [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…4,7,9 Current Study Abstinence has long been considered a stable outcome for individuals with AUD, 14,15 and numerous studies have questioned whether "controlled" drinking can be maintained. [15][16][17] The debate over whether controlled drinking is achievable has been considered in the academic literature for nearly 50 years, 18 but concrete guidance has not emerged on the magnitude of the reduction that is necessary for sustained health benefits. More recent work has shown that drinking reductions, as assessed by the WHO RDLs, are often seen over the first post-treatment year, 7 but whether these reductions can be maintained for longer periods and whether WHO RDL reductions, short of abstinence, are associated with sustained improvements in functioning remain unclear.…”
Section: Defining "Success" In Aud Treatmentmentioning
confidence: 99%